DESIGNING LEARNING CONCEPTS AFTER THE PANDEMIC: BLENDED LEARNING MS. TEAMS COMBINATION WITH MOODLE - Roni Wiranata; Siti Aisyah (Asosiasi Pengelola Publikasi Ilmiah (APPI) PT PGRI, 2022)
Learning in the classroom turned into a prevailing design after the pandemic. The impact of this pandemic bears it exceedingly problematic for students and teachers to adopt. However, almost 2 years of online learning can cause people to be too comfortable studying at home even though it’s realized that this is very ineffective for them. In this study, the students of STKIP PGRI Lumajang after implementing the distance learning program in collaboration with STKIP BIMA. Purpose of this study was to understand the problems of online learning for STKIP PGRI Lumajang students during implementing PJJ funded by the ministry to support MBKM and to understand online learning strategies after the pandemic. Method in this research is a qualitative approach where student informants of STKIP PGRI Lumajang method of data collection are carried out by hidden interviews inserted during lectures and closed interviews for STKIP PGRI Lumajang students after implementing PJJ with partner campuses, and always making observations to innovate in PJJ. The result in the even semester of the 2021/2022 academic years is known that distance learning is indeed very effective in urban areas or those with stable internet networks. However, this is in contrast to education providers whose areas have network difficulties. Constraints on the availability of electricity, and devices learning. The most problems are network problems and internet quota, the problem of partner students having difficulty understanding learning applications. So we blend the conclusion and suggested design for PJJ education provides learning, to hope to be able to provide easy access for learners